Representations of Israeli–U.S. Relations in U.S. News Media at the Height of the Israel–Hamas Conflict: A Semantic Prosody Analysis - Dimas Raditya Bagaskara; Muhammad Farihul Qulub; Saddam Reza Hamidi (Translation and Linguistics (Transling), 2026)
Underlying sociopolitical and power dynamics influence the formation of discourses. Due to its cultural traces, the prevalence of Western elements in English textbooks is not exactly novel. However, the question remains whether the Western elements in English textbooks have any social implications, particularly the issue of Global English in the EFL landscape. Thus, this study examines the representation of Western cultural elements found in Indonesian English textbooks across two curricula and their implication towards Global English using critical discourse analysis. The results concluded that both textbooks represent Western-centric elements differently in the text, discursive, and social practice layers. Despite that, both textbooks consistently privilege Western values and cultures. Such representations challenge Global English principles that emphasises on cultural identity. Moreover, the findings also highlight how the representation of Western elements in both textbooks could cause cultural mismatches that make it harder for the students to internalise. The present study advocates the need for balanced materials that incorporate both Western elements and local cultures to nurture cultural identity, which is the core principle of Pancasila ideology that is used as the basis to create the Indonesian educational curricula.